2015
DOI: 10.1016/j.solmat.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of copper diffusion in gallium arsenide solar cells for space applications

Abstract: High efficiency, thin-film Epitaxial Lift-Off (ELO) III-V solar cells offer excellent characteristics for implementation in flexible solar panels for space applications. However, the current thin-film ELO solar cell design generally includes a copper handling and support foil. Copper diffusion has a potentially detrimental effect on the device performance and the challenging environment provided by space (high temperatures, electron and proton irradiation) might induce diffusion. It is shown that heat treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
0
15
1
Order By: Relevance
“…The significant decrease in J sc observed for the thin-film cells on Cu carriers is in sharp contrast with the small changes (typically 1-2%) observed for cells on an Au carrier and substrate-based cells with and without Cu (both in this study and in previous work [34], [35], [40]). This indicates that the degradation process causing the decrease in J sc is specific for thin-film cells on a Cu carrier and therefore of interest for further investigation.…”
Section: B Characterization and Accelerated Life-time Testingcontrasting
confidence: 94%
See 1 more Smart Citation
“…The significant decrease in J sc observed for the thin-film cells on Cu carriers is in sharp contrast with the small changes (typically 1-2%) observed for cells on an Au carrier and substrate-based cells with and without Cu (both in this study and in previous work [34], [35], [40]). This indicates that the degradation process causing the decrease in J sc is specific for thin-film cells on a Cu carrier and therefore of interest for further investigation.…”
Section: B Characterization and Accelerated Life-time Testingcontrasting
confidence: 94%
“…Unfortunately experimental determination is difficult and hence there are very few activation energies reported for solar cell degradation [29], [32], [33] and none of these concern (Cu) diffusion. The European Cooperation for Space Standardization (ECSS) standard for In previous studies [34], [35] a substrate-based model system utilizing a 45% coverage front contact grid was used to investigate the effects of Cu diffusion on GaAs solar cells. In these studies it was shown that at temperatures < 250 ○ C Cu diffusion has no significant effect on the J-V characteristics of (substrate-based) solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study 37 it was found that heat treatments indeed induce Cu diffusion, but no influence of electron irradiation on the diffusion process was observed. Therefore subsequent research was focussed primarily on investigating the temperature dependent degradation mechanism(s) causing solar cell degradation as a result of copper diffusion.…”
Section: Introductionmentioning
confidence: 92%
“…al 38 is used. Subsequently the test could be extended to 10, 44 or 66 hours in further experiments whenever required 37 . Unfortunately ELO cells appear to be incompatible with the accelerated ageing test at temperatures ≥ 200 • C 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Cu has also been used as a part of the back side contact in GaAs solar cells, but Cu is also known to diffuse easily into III-V semiconductors and thus to reduce the V oc . [20][21][22] In our approach, we have studied GaInNAs solar cells with double-layer Ag/Cu reflectors exhibiting high reflectance, good adhesion, and low contact resistance. Moreover, a thin Ag layer acts as a diffusion barrier, preventing Cu diffusion into the semiconductor structure even when the cell is subjected to thermal annealing.…”
mentioning
confidence: 99%